Occupancy-frequency distribution of birds in land-sharing and -sparing urban landscapes in Europe - Suhonen Jukka; Jokimäki Jukka; Kaisanlahti-Jokimäki Marja-Liisa; Morelli Federico; Benedetti Yanina; Rubio Enrique; Pérez-Contreras Tomás; Sprau Philipp; Tryjanowski Piotr; Møller Anders Pape; Díaz Mario; Ibáñez-Álamo Juan Diego (ELSEVIER, 2025)
Species richness is a widely used proxy for patterns of biodiversity variation in metacommunities. However, deeper analyses require additional metrics, such as the occupancy-frequency distributions (SOFD) of different local communities. The SOFD patterns indicate the number of shared species between study sites; therefore, they can provide new insights into the current debate on how to create more biodiversity-friendly cities. Breeding birds were counted from 593 point-count stations located in five 500 m x 500 m squares in land-sharing (LSH; low-density built areas interspersed with green spaces) and five similar nearby squares in land-sparing (LSP; densely built-up with set-aside, large-sized, continuous green spaces) landscapes in nine cities across Europe. High beta-diversity (with over 42% of the 103 species detected being restricted to a single city and only 7% found in all studied cities) showed the uniqueness of cities at the continental scale. Urban bird metacommunities followed the unimodal-satellite SOFD pattern at the European continental scale but a bimodal symmetric or asymmetric distribution at the city-level scale, suggesting that many common species occur in cities on a smaller scale. The LSP urban areas followed a unimodal satellite SOFD pattern with numerous rare species. In contrast, the LSH areas fit several types of bimodal SOFD patterns equally well, where communities share several common species. The findings also highlight the need to use multi-scale approaches to analyze the effects of LSH-LSP urban designs on urban bird diversity.